The Rationale Underlying the Functional Currency Choice. - Revsine, Lawrence (The Accounting Review, 1984)
ABSTRACT: FASB Statement No. 52 on Foreign Currency Translation is designed to achieve compatibility between financial statement numbers and underlying economic effects of exchange rate changes. This result is accomplished through the selection of what the FASB terms the functional currency of the foreign subsidiary. Unfortunately, the rationale underlying the functional currency choice is complicated and not widely understood. To overcome the problem, this paper explains the objectives behind the functional currency choice by using three illustrative case settings.